Do Abrasion- or Temperature-Based Techniques More Effectively Relieve Physical Dormancy in Seeds of Cold Desert Perennials? - Kildisheva, O.; Erickson, T.; Merritt, David; Madsen, M.; Dixon, Kingsley; Vargas, J.; Amarteifio, R.; Kramer, A. (Society for Range Management, 2018)
Seed dormancy can present a significant barrier to restoration outcomes in dryland systems. Physical and combinational (physical + physiological) dormancy are prevalent among seeds of many herbaceous perennials used in restoration of drylands throughout the western United States. Although many techniques designed to alleviate these dormancy traits exist, their efficacy is species specific, may result in embryo damage, and may have limited large-scale application. To identify the most effective means of dormancy alleviation with the potential to be used on an operational scale, we examined the effects of 16 temperature-based techniques (altering temperature and duration of wet heat, freezing and wet heat, and freeze-thaw cycles) and 6 abrasion-based techniques (altering pneumatic scarification length or using a single duration of manual scarification) on the enhancement of seed permeability among two physically dormant (western prairie clover [Dalea ornata Douglas Eaton & Wright] and Munro's globemallow [Sphaeralcea munroana Douglas Spach] ) and two combinationally dormant species (basalt milkvetch [Astragalus filipes Torr. ex A. Gray] and longspur lupine [Lupinus arbustus Douglas ex Lindl.] ). We first assessed seed imbibition following exposure to all temperature- and abrasion-based techniques to identify those most successful at promoting seed permeability and then evaluated the effectiveness of those techniques through a series of germination experiments. For combinationally dormant species, we also tested whether exposure to GA 3 enhanced germination. Abrasion-based techniques were more effective than temperature-based techniques at improving water uptake across all species. Pneumatic scarification significantly improved germination, but optimal treatment durations were species specific. GA 3 did not enhance germination under the tested conditions. We conclude that pneumatic scarification is a fast, safe, and effective method for alleviating physical seed dormancy with a potential to be scaled up for operational use in restoration.